A binary plant vector strategy based on separation of vir- and T-region of the Agrobacterium tumefaciens Ti-plasmid - Hoekema, A.; Hirsch, P.R.; Hooykaas, P.J.J.; Schilperoort, R.A.
The soil bacterium Agrobacterium tumefaciens is a plant pathogen that causes crown-gall tumours after infection of wounded dicotyledonous plants. Large plasmids (Ti-plasmids)are responsible for the oncogenicity of the bacterium. Crown-gall tumours contain a DNA segment, called the T-DNA, which is homologous with a defined part of the Ti-plasmid present in the tumour-inducing bacterium, and is stably integrated into the plant genome. Apart from the T-DNA another region of the Ti-plasmid, called the vir-region, is essential for tumour induction. We report here the interaction of two compatible plasmids, one containing the vir-region, the other carrying the T-DNA on a wide host-range replicon. An A. tumefaciens strain harbouring both plasmids has a normal tumour-inducing capacity, although neither plasmid is functional alone. With this approach, the T-DNA on one plasmid can, because of its size, be easily genetically manipulated using Escherichia coli as a host. Transfer of this plasmid into an A. tumefaciens strain harbouring the plasmid with the vir-region allows introduction of the manipulated T-DNA into plant cells. In this way, sophisticated binary vector systems for plant genetic engineering can be developed.
Keywords: AGROBACTERIUM TUMEFACIENS; CARCINOGENICITY; ESCHERICHIA COLI; GENETIC ENGINEERING; HEREDITY; HIGHER PLANT; INTERACTION; NONHUMAN; PLANT; PLASMID; SEPARATION; VECTOR